Comparison of freely dissolved concentrations of PAHs in contaminated pot soils under saturated and unsaturated water conditions - Nora Bartolomé and Isabel Hilber and Rainer Schulin and Philipp Mayer and Gesine Witt and Mathias Reininghaus and Thomas D. Bucheli (The science of the total environment, 2018)
Passive sampling (PS, equally used for passive sampler) methods have successfully been applied in situ to quantify the bioavailability of hydrophobic organic compounds in air, water and sediments. However, very little is known on the applicability of PS in unsaturated soils. Here, we present the results of a greenhouse experiment in which we applied in situ PS methods in pots. Low density polyethylene (LDPE) and polydimethylsiloxane (PDMS) fibres with a newly developed PS holder were used to analyse freely dissolved polycyclic aromatic hydrocarbon (PAH) concentrations (Cfree) in a skeet shooting range soil and an uncontaminated control soil under water saturated and unsaturated conditions for up to nine months. A short exposure time of three months was not sufficient for the PDMS samplers to reach distribution equilibrium with the surrounding soil. Under saturated water conditions, the in situ results agreed well with measurements obtained from the conventional ex situ soil suspension method. They were in accordance with similar comparisons made in previous studies on sediments, as well as with model predictions. However, for unsaturated water conditions, the results differed considerably from the ex situ Cfree values, in particular for the light molecular weight (LMW) PAHs such as phenanthrene, fluoranthene, and pyrene. The results of the two in situ PS methods were in good agreement with each other under both soil water conditions, indicating that dissipation mechanisms, such as degradation or volatilization, led to a substantial decrease in Cfree under unsaturated conditions, especially for the LMW PAHs (log10KOW?<?5.85) over a period of six months or more. Thus, in their current state of development, in situ PS methods can be used in soils under water-saturated conditions. However, an adequate method to correct for non-equilibrium conditions needs to be developed before they can be applied to unsaturated conditions, mainly for LMW PAHs.
Keywords: Passive sampling; Bioavailability; Risk assessment; In situ; Ex situ; Soil pore water